2003
DOI: 10.1093/ndt/gfg074
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in end-stage renal disease: an emerging threat to patient outcome

Abstract: It is important to consider oxidative stress as a potentially important source of patient morbidity and mortality, although this knowledge is not yet immediately applicable in the clinical arena. Further well-designed, randomized controlled clinical trials with anti-oxidants (e.g. vitamin E, vitamin C, N-acetyl cysteine, L-arginine) are required to establish evidence-based recommendations for clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
515
2
44

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(572 citation statements)
references
References 41 publications
11
515
2
44
Order By: Relevance
“…In the present study, we observed that HD significantly increased total peroxide concentration in both groups, whether they received iv.Fe or not. Peroxide generation in our ESRD patients therefore seemed not to be correlated to iv.Fe administration; the observed increase is more likely to result from other sources of oxidative stress related to HD (22).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the present study, we observed that HD significantly increased total peroxide concentration in both groups, whether they received iv.Fe or not. Peroxide generation in our ESRD patients therefore seemed not to be correlated to iv.Fe administration; the observed increase is more likely to result from other sources of oxidative stress related to HD (22).…”
Section: Discussionmentioning
confidence: 88%
“…There is wide agreement that patients who undergo regular HD treatment experience increased oxidative stress (22). NTBI in the circulation could in principle participate in redox reactions that give rise to reactive oxygen species.…”
mentioning
confidence: 99%
“…A variety of heterogeneous ischemic conditions, including endothelial and extracellular hypoxia, acidosis, free radical injury, and sodium and calcium pump disruptions, have been associated with rapid modifications of the cobalt binding properties (47)(48)(49). Therefore, IMA should not be regarded as a specific cardiac marker, especially in patients suffering from diseases associated with enhanced oxidative stress, such as uremia (50), where the balance between prooxidant and antioxidant capacities is conventionally shifted toward an increased oxidative stress (51,52). Moreover, HD is often associated with adverse ischemic effects, such as arteriovenous (AV) access-related ischemia and hypoperfusion (53), which results from dialysis-induced alterations in oxygen delivery and myocardial oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In CRF, not only the usual cardiovascular risk factor but also those unique to uremia increases oxidative stress [1][2][3][4][5][6][7]. In the presence of oxidative stress, free oxygen radicals attacks the functional molecules, such as proteins, lipids and DNA, either denaturing them or altering their structure.…”
Section: Introductionmentioning
confidence: 99%